2017
DOI: 10.13031/jash.11753
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Work Demand and Gender on Occupational and Psychosocial Stress in Hispanic Farmworkers

Abstract: Hispanic farmworkers experience hazardous work conditions, language barriers, poverty, and limited healthcare access that increase their risk for health problems. We sought to characterize occupational and lifestyle stressors in farmworker couples and to examine the impact of seasonal work demand and gender on health outcomes. We administered surveys to 31 couples (N = 62) in May (low work demand) and September (high work demand) of 2012. Measures included acculturation, perceived stress, depressive symptoms, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Our findings support and extend the limited research on Latina farmworker mental health. To our knowledge, most research has been conducted in migrant and seasonal Latina farmworkers in North Carolina, Colorado, and Oregon and all before the onset of the COVID-19 pandemic [16][17][18][19]. In our study, we found nearly 40% of Latina farmworker respondents with stress scores indicative of significant mental health concerns.…”
Section: Discussionmentioning
confidence: 53%
“…Our findings support and extend the limited research on Latina farmworker mental health. To our knowledge, most research has been conducted in migrant and seasonal Latina farmworkers in North Carolina, Colorado, and Oregon and all before the onset of the COVID-19 pandemic [16][17][18][19]. In our study, we found nearly 40% of Latina farmworker respondents with stress scores indicative of significant mental health concerns.…”
Section: Discussionmentioning
confidence: 53%
“…Even with exposures to occupational hazards and injury rates as high as 12.5%, farmworkers lack occupational health standards and fair labor laws [ 4 , 5 ]. Farmworkers face low socioeconomic factors, including high rates of poverty, low levels of educational attainment, and inadequate housing conditions [ 6 , 7 ]. Despite being an essential labor force, farmworkers encounter barriers to accessing health care in the U.S.…”
Section: Introductionmentioning
confidence: 99%
“…These analyses indicated that sexual harassment is commonly experienced by women working in agriculture. Another set of studies has focused more on the job characteristics of women agricultural workers [43,56,57]. These studies used diverse methods to examine different aspects of work organization and work safety culture.…”
Section: Introductionmentioning
confidence: 99%